Theoretical Perspectives on Cultural Representations in Vietnamese Children’s Picturebooks - Ngoc Tai Huynh (Cambridge Scholars, 2023)
This book evaluates the implicit and nuanced meanings embedded in Vietnamese picturebooks and explores the intricate cultural aspects they portray. Through meticulous research, the contributors of this pioneering book unveil the values of contemporary Western analytical frameworks while identifying their limitations. By combining East Asian philosophies with captivating visual texts, this groundbreaking work offers reliable theoretical and practical resources, enabling a profound exploration of Vietnamese culture.